Volume 11: Wind Energy 2022
DOI: 10.1115/gt2022-82268
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Post-Stall Extrapolation and Rotational-Augmentation Models on the Performance of Stall-Controlled Wind Turbines

Abstract: While most wind energy comes today from utility-scale machines, small wind turbines SWTs can still play a role in off-grid installations or in the context of distributed production and smart energy systems. Due to cost reasons, SWTs (especially up to 100kW) are usually controlled via progressive stall of the blades. Accurate airfoils polars are therefore key in engineering simulation models, not only to ensure predictive blade performance, but are also pivotal for proper controller tuning and an effective eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For the purposes of the present study, it is worth noting that the turbine has been originally designed using airfoil polars extrapolated with the Montgomerie method [10] and corrected for rotational-augmentation with the Bak's method [11]. The reader is referred to the GitHub repository for any additional detail about the turbine; a detailed explanation of the variable speed, stall-control strategy can be also found in [12].…”
Section: Case Studymentioning
confidence: 99%
“…For the purposes of the present study, it is worth noting that the turbine has been originally designed using airfoil polars extrapolated with the Montgomerie method [10] and corrected for rotational-augmentation with the Bak's method [11]. The reader is referred to the GitHub repository for any additional detail about the turbine; a detailed explanation of the variable speed, stall-control strategy can be also found in [12].…”
Section: Case Studymentioning
confidence: 99%
“…However, the author themselves recognized the necessity of further investigation in order to generalize the methodology, particularly for larger rotors. Using the UNIFI experimental turbine, recently developed by Università degli Studi di Firenze, Papi et al [19] evaluated the impact of poststall extrapolation methods with particular attention on the stall delay effects. The results showed that the impact of the methodology was significant therefore the designers should pose more attention to a wise selection of the method used for post-stall extrapolation.…”
Section: Introductionmentioning
confidence: 99%